Eosinophilic Vulvar Leukoderma - Kaya Nakada; Shiro Niiyama; Toshiaki Oharaseki; Hidetsugu Fukuda (Karger Publishers, 2021)
We report the case of a 54-year-old woman with asthma and atopic dermatitis who presented a white spot on the genitalia. Histologic examination showed numerous eosinophils in the epithelium and the dermis. Eosinophilic esophagitis is defined as an esophageal disease characterized clinically by symptoms related to esophageal dysfunction and histologically by an eosinophil-predominant inflammation. We discuss the possible relationship between the two diseases.